Manajemen Dakwah Program Kisah Menawan Sang Teladan di Radio Rodja 75,6 AM Bogor - Muhammad Samih Rozin; Fatmawati Fatmawati (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2018)
The development of today's communications media has enabled people around the world to communicate with each other. This study aims to find out how the pre-production process of the Captivating Story of the Exemplary Program, how the process of implementing the production of the Captivating Story of the Exemplary, and how the evaluation process in the Program Story of the Model in Radio Rodja. This research uses qualitative approach. The research method used by the author is descriptive analysis. Descriptive method aims to describe the systematic facts or characteristics of a particular population or field in a fact and accurate. In other words, this method analyzes and interprets the meaning of the data. In the program of the captivating story of the exemplar through several stages: pre production includes: ideas, format planning, broadcast materials, performers, program name, and time of broadcast. The production process includes: the implementation of broadcasting, production materials, production executors, and facilities and infrastructure. Post production is weekly evaluation and the whole team